The Moderating Role of Electronic Word of Mouth in the Relationship Between User-Generated Content and Purchase Decisions - Bagus Yunianto Wibowo; Nanang Adie Setyawan; Destine Fajar Wiedayanti; Irin Mirrah Luthfia; Mona Inayah Pratiwi (Jurnal Teknologi dan Manajemen Industri Terapan, 2025)
This research is a quantitative study with an explanatory approach, namely an approach that relies on previous research for three purposes, namely: creating hypotheses, creating new variations on hypotheses that are different from previous research, and proving hypotheses. The data used in this study are primary data that researchers obtained from sources that are definitely credible in the form of Three Second customers, with a total of two hundred customers spread throughout Indonesia. The data that researchers obtained were analyzed using the innovative PLS 4.0 analysis tool. The conclusion is explained comprehensively in this section. In the first hypothesis in this article, it can be concluded that it is accepted and proven. This is because the P-values in this article are positive and below the 0.05 significance level, namely 0.007. The results mentioned by the researcher above are in line with a number of previous studies, namely. This means that better user-generated content on a product can make a larger market share, increase product recognition in the eyes of the public, and so on, which can increase Purchasing Decisions. In the following hypothesis, the Electronic-Word of Mouth variable can strengthen or moderate the influence of the User Generated Content variable on Purchasing Decisions because the same thing, namely the P-Value value, is positive and below the 0.05 significance level, namely 0.000. more significant than direct testing of 0.007. Thus, it can be concluded that the first and second hypotheses in this article can be accepted.